The Evolution and Impact of AI on EdTech Business Models - Per Andersson; Christopher Rosenqvist (International Telecommunications Society (ITS), 2024)
This paper investigates the transformative role of Artificial Intelligence (AI) in shaping Education Technology (EdTech) business models, focusing on key components such as value creation, delivery, and capture. Through qualitative analysis and detailed case studies of companies like Sensavis, Duolingo, Byju's, and Coursera, we examine how AI integration drives personalized learning and optimizes educational delivery. Our findings highlight the dynamic nature of EdTech business models, emphasizing the necessity for continuous innovation and strategic adaptation in response to AI advancements. We conclude with potential AIdriven scenarios for future education, exploring their implications for EdTech business models and the broader educational landscape.
Keywords: 330; Education Technology (EdTech); Business Model Innovation; Artificial Intelligence (AI); Digital Transformation; Personalized Learning